On the almost-everywhere convergence of the Riesz means of double orthogonal series - Andrienko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish coefficient conditions of the classical type that guarantee the almost-everywhere summability of double orthogonal series by the Riesz methods of nonnegative order. We also prove certain equiconvergence theorems.